Ciliated hepatic foregut cyst: a rare diagnosis behind a hepatic cyst - Andrade, Rita; Amaral, Maria João; Serôdio, Marco; Prior, Inês; Tralhão, José Guilherme (International Surgery Journal, 2026)
Ciliated hepatic foregut cysts (CHFC) are rare and typically benign lesions of the liver derived from an embryonic remnant of foregut epithelium. Patients are almost always asymptomatic and mostly incidentally found on radiologic studies. Radiographic imaging is usually insufficient for diagnosis and definitive diagnosis is made through histology. It is important to consider this condition in the differential diagnosis of liver lesions, particularly those located in the subcapsular region of the segment 4. Usual diagnostic uncertainty and a malignant potential that cannot be totally excluded, surgical excision should be considered. We describe a case of a 76-year-old male with an atypical cystic mass in segment 4 of the liver who underwent a laparoscopic resection. Histology revealed a ciliated hepatic foregut cyst.